Community Service of PGMI Students in Strengthening IPAS Learning Materials through Canva at MI Miftahul Huda 2 Palangka Raya - Puput Melati Sukma; Ratna Kartika Sari; Muhammad Hairil; M Sabrina; Sulistyowati Sulistyowati; Zaitun Qamariah; Hadma Yuliani (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Community service represents a tangible contribution of higher education institutions in improving the quality of learning at the elementary level. This service activity was carried out collaboratively by lecturers and students at MI Miftahul Huda 2 Palangka Raya with the aim of enhancing the quality of IPAS (Ilmu Pengetahuan Alam dan Sosial) learning through the development of interactive teaching materials based on Canva. The program applied the Asset-Based Community Development (ABCD) approach, which emphasizes the empowerment of existing assets within the school community. The implementation involved mentoring sessions, technical guidance, and direct classroom application of the developed materials. Effectiveness was evaluated through pretests and posttests, showing an increase in students' understanding from an average pretest score of 55.19 to a posttest score of 77.04, with an average N-Gain of 0.47 (moderate category). Validation results from subject matter experts (96%), design experts (97%), and classroom teachers (89%) confirmed that the developed media were appropriate in terms of content, visual quality, and language use. In addition to improving learning outcomes, the use of technology-based teaching media also increased student motivation and teacher engagement during the learning process. The outcomes of this program not only provided direct benefits to the partner school but also demonstrated the potential for broader application as a participatory and sustainable model for digital innovation in basic education.